STUDY OF THE POPULATION DYNAMICS OF DOLYCORIS INDICUS STAL AND THE IMPACT OF INFESTATION ON THE HOST PLANTS - KUMAR, SURENDER; CHATTERJEEE, V.C.; ., INDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
In Dolycoris indicus Stal breeding is maximum in Summer months and it appears in early March on Trifolium alexandrium Linn. After the crop is over, in the absence of suitable host plant it shifts to Cannabis sativa Linn. Due to its polyphagous nature and food preference at the milky stage. it soon migrate on the paddy during rainy season. Its maximum population has been observed on the first i.e. T. alexandrium and Oryza sativa Linn. plants. Seeds after collection are separated into healthy and infested ones and the percentage damage to each crop is 34.65% (in T. alexandrium) and 58.8% (in O. sativa).